Disc‐shaped nanocrystal model for simulating the diffraction peak profile from a one‐dimensional superlattice and its application to Pt/AlN superlattice films. Issue 3 (16th May 2016) - Harumoto, Takashi; Sannomiya, Takumi; Muraishi, Shinji; Shi, Ji; Nakamura, Yoshio
Abstract : On the basis of the film structure of a Pt/AlN multilayer film which exhibits a superlattice peak after annealing, a disc‐shaped nanocrystal model is proposed for simulating the diffraction profile from a one‐dimensional superlattice, and the effects of the in‐plane crystal size and the orientation distribution on the profile are discussed. Abstract : On the basis of the film structure of a Pt/AlN multilayer film which exhibits a superlattice peak after annealing, a disc‐shaped nanocrystal model is proposed for simulating the diffraction line profile from a one‐dimensional superlattice. The proposed model demonstrates that a superlattice peak can arise even from just two disc‐shaped nanocrystals and even with a large misorientation (a few degrees), provided both the thickness and the in‐plane crystal size of the nanocrystals are of the order of nanometres. Using the model, the superlattice peaks from Pt/AlN superlattices are analysed quantitatively and the effect of annealing on the film is discussed.